Evaluation of The Feasibility of Wood Working Construction Workshop - Rozi, Muhammad Fahrul; Haq, Syaiful (Universitas Negeri Padang, 2024)
This study aims to determine the feasibility level of the Wood Work Construction Workshop of the Civil Engineering Department of FT UNP based on the standards of Permendiknas number 40 of 2008, SNI 03-6575-2001, and ISO 9001: 2008. This research approach uses descriptive qualitative research methods and uses a policy evaluation model. The object of this research is the wood working construction workshop. Data collection techniques were carried out by means of observation, interviews, direct measurement and documentation. The research instrument used a checklist that was used during direct measurement. The technique of obtaining data uses a roller meter, lux meter, sound level meter, thermometer and anemometer. The results of this study are the workshop area according to the standard, the area of hand wood working area according to the standard, the area of wood machinery according to the standard, the area of storage and technician areas according to the standard, the lighting level of the wood workshop in the morning according to the standard, at noon according to the standard, and in the afternoon not according to the standard, workshop natural ventilation air circulation for air temperature in the morning is up to standard, in the afternoon and evening is not up to standard, air humidity in the morning and afternoon is up to standard, in the afternoon is not up to standard, air velocity in the morning and afternoon is not up to standard, in the afternoon is up to standard, sound and noise are up to standard, room temperature in the morning is up to standard, The number of students is according to the standard, the number of technicians is not according to the standard, the implementation of workshop practice is according to the standard, the color of the room is according to the standard, the wood workshop practice equipment for hand tools is according to the standard, the working station tool of the type of tool consists of 4 types not according to the standard and 8 types are according to the standard, Workshop facilities for furniture are according to the standard, educational media are according to the standard, fire protection equipment is not according to the standard, first aid kits are according to the standard, personal protective equipment is not according to the standard, workshop support equipment for electrical contact boxes are according to the standard, trash cans are not according to the standard, information data boards are according to the standard, vacuum is not according to the standard.